Boredom, shanzhai, and digitization in the time of creative China - Kloet, Jeroen de; Chow, Yiu Fai; Scheen, Lena (Asian visual cultures., 2019)
With its emergence as a global power, China aspires to transform from "made in China" to "created in China". Mobilised as a crucial source for solid growth and "soft power", creativity has become part of the new China Dream. This anthology engages with the imperative of creativity by aligning it to three interrelated phenomena: boredom, shanzhai, and digitisation. How does creativity help mitigate boredom? Does boredom incubate creativity? How do shanzhai practices and the omnipresence of fake stuffs challenge notions of the original and authentic? Which spaces for expressions and contestations has China's fast-developing digital world of Weixin, Taobao, Youku and Internet Plus Policy opened up? Are new technologies serving old interests? Essays, dialogues, audio-visual documents and field notes, from thinkers, researchers, practitioners and policy-makers, contribute to explore, examine and problematize what is going on in China now, ultimately to tease out its implication to our understanding of "creativity."